Penerapan Retorika Visual dalam Iklan Indomie Korean Ramyeon Series X NewJeans di Media Youtube - Zahra Namira Wandi; Pudji Muljono; Fahmi Fuad Cholagi (Penerbit Jurnal Indonesia, 2025)
Digital advertisement has evolved into one of the main marketing communication tools in the digital era. YouTube is one of the largest social media platforms and the primary choice for major companies to market their products. One strategy that attracts the audience's attention is through brand collaborations with public figures. Indomie partnered with NewJeans as the Global Brand Ambassador for its latest Korean Ramyeon Series product advertisement. This study aims to analyze the visual elements that can build a persuasive message and apply the conditions and characteristics within the visual rhetoric theory. This research uses a descriptive qualitative method based on Foss's (2005) visual rhetoric theory to evaluate three conditions of visual rhetoric: symbolic, human intervention, and the presence of an audience. This research analyzes three characteristics of visual rhetoric: nature of the image, function of the image, and evaluation of the image, to understand how visual elements shape messages and influence the audience. The results show that this advertisement successfully applies the principles of visual rhetoric according to Foss's theory (2005). The visual elements in this advertisement are symbolic, with the use of colours, facial expressions, and visual style strengthening the product message. Human intervention is evident in the creative visuals relevant to the target audience, namely Generation Z. The advertisement also manages to evoke a positive communicative response. The analysis of visual rhetoric characteristics reveals the effective application of the nature of the image, the function of the image, and the evaluation of the image in shaping a persuasive message and strengthening emotional connections through the effective use of visual elements.